2014
DOI: 10.1016/j.jcrs.2013.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Light transmittance of 1-piece hydrophobic acrylic intraocular lenses with surface light scattering removed from cadaver eyes

Abstract: Although surface light scattering of explanted IOLs was significantly higher than that of controls and appeared to increase with time, no effect was observed on light transmittance of 1-piece hydrophobic acrylic IOLs with or without a blue-light filter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Interestingly, previous reports on light transmittance using AcrySof lenses with glistening and SSNG did not find any decrease18, 19 and seem to contradict our findings. In their studies, an integrated sphere type spectrophotometer (Lambda 35 UV/Vis spectrophotometer, PerkinElmer Inc.) was used; however, we used a double beam spectrophotometer and this may explain the difference in findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, previous reports on light transmittance using AcrySof lenses with glistening and SSNG did not find any decrease18, 19 and seem to contradict our findings. In their studies, an integrated sphere type spectrophotometer (Lambda 35 UV/Vis spectrophotometer, PerkinElmer Inc.) was used; however, we used a double beam spectrophotometer and this may explain the difference in findings.…”
Section: Discussioncontrasting
confidence: 99%
“…27 Staining with Coomassie blue G-250 can confirm protein removal, and, if required, proteins may be eliminated with treatment with a mixture of enzymes (subtilisin A and trypsin), a chelator (ethylenediaminetetraacetic acid), and with a solution of 0.6% sodium hypochlorite in phosphate-buffered saline; in this case, the residual stain should be removed by treating the IOL with a 0.6% sodium hypochlorite solution and then rinsing in distilled deionized water. [55][56][57] As glistening and SSNGS are temper- Gross photograph of the explanted lens in the dry state (320). (B) Light photomicrograph of the dry lens (3400).…”
Section: Methods For Iol Evaluationmentioning
confidence: 99%
“…51 Thus, the IOL analysis should be performed both in dry and hydrated states for comparative purposes. 55 If the lens is delivered in a dry state, it should be rehydrated in balanced salt solution for 24 hours at room temperature for evaluation in a hydrated state. 55 However, for transportation, the IOL is usually placed in balanced salt solution or distilled water.…”
Section: Methods For Iol Evaluationmentioning
confidence: 99%
“…Indeed, this occurred in the study by Michelson et al 1 in which a decrease in transmission was found when the IOLs, which had been explanted because of opacification, were analyzed using a spectrophotometer with an integrating sphere. On the contrary, as we pointed out above, Werner et al 5 found variation in the scattering, but not in the transmittance, when they studied surface light scattering in IOLs removed from cadaver eyes.…”
Section: Introductionmentioning
confidence: 65%
“…2 Glistenings are fluid-filled microvacuoles that form inside the intraocular lens optic when the IOL is in an aqueous environment, thereby producing an internal light scattering which is difficult to distinguish from surface light scattering. [2][3][4] Werner et al, 5 when analyzing some one-piece hydrophobic acrylic IOLs removed from cadaver eyes, demonstrated that surface light scattering significantly increased when compared with scattering in IOLs that had not been used, but their transmittance did not vary. Although the controversy continues, it seems that the cause of light scattering on the surface of hydrophobic acrylic IOLs (referred to by some authors as whitening) is due to a trace of water molecules that infiltrate the optic.…”
Section: Introductionmentioning
confidence: 99%